2005
DOI: 10.1111/j.1365-2141.2005.05418.x
|View full text |Cite
|
Sign up to set email alerts
|

Does cryosupernatant plasma improve outcome in thrombotic thrombocytopenic purpura? No answer yet

Abstract: Summary A randomized prospective trial compared cryosupernatant plasma (CSP) to fresh frozen plasma (FFP) for treatment of thrombotic thrombocytopenic purpura (TTP). A total of 236 patients were required: 28 patients were treated with CSP and 24 with FFP within 30 months. There were no differences in survival at 1 month. By day 9, 17 of 26 patients with CSP and 18 of 24 with FFP had a platelet count >100 × 109/l. At entry, von Willebrand factor (VWF) multimers were normal in all patients (range 1·1–3·95 IU/ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 26 publications
2
63
1
3
Order By: Relevance
“…However, the Canadian Apheresis Group recently performed a randomized, prospective trial to assess whether cryosupernatant is better than fresh frozen plasma as replacement fluid for PE [8]. Patients received 7 PEs during the first 9 days; antiplatelet therapy was optional while steroid were prohibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Canadian Apheresis Group recently performed a randomized, prospective trial to assess whether cryosupernatant is better than fresh frozen plasma as replacement fluid for PE [8]. Patients received 7 PEs during the first 9 days; antiplatelet therapy was optional while steroid were prohibited.…”
Section: Discussionmentioning
confidence: 99%
“…Cryosupernatant was used based on a pilot study by the Canadian Apheresis Group suggesting that this replacement fluid was more effective than fresh frozen plasma [7]. However, a subsequent, randomized study by the same group failed to confirm this finding and concluded that the two treatments were equivalent [8].…”
Section: Methodsmentioning
confidence: 99%
“…Cryosupernatant is the blood product which is the remnant after separating cryoprecipitate. Cryosupernatant is deficient in vWF and rich in ADAMTS13, so theoretically plasma exchange using cryosupernatant is better than plasma exchange with FFP, however large clinical trials are needed to prove its practical effectiveness [9]. All the children in this series responded well to treatment with cryosupernatant.…”
Section: Discussionmentioning
confidence: 91%
“…A subsequent, as yet unpublished work, in which we treated 26 patients with SDP and 34 with CSP also failed to show a difference in outcome although, again, it must be stressed that statistical significance was not achieved and it will require very large numbers of patients (probably > 200) to compare mortality in these two forms of therapy. As we previously stated (Rock et al, 2005) -without large numbers of patients -no answer yet. …”
mentioning
confidence: 98%
“…In our paper (Rock et al, 2005), we described a study that was designed to compare cryosupernatant plasma (CSP) with fresh frozen plasma (FFP) in the treatment of TTP. The study was designed to enter a total of 236 patients, but was halted due to a lack of funding after only 52 patients were entered.…”
mentioning
confidence: 99%